2010
DOI: 10.1186/1465-9921-11-7
|View full text |Cite
|
Sign up to set email alerts
|

Mouse models to unravel the role of inhaled pollutants on allergic sensitization and airway inflammation

Abstract: Air pollutant exposure has been linked to a rise in wheezing illnesses. Clinical data highlight that exposure to mainstream tobacco smoke (MS) and environmental tobacco smoke (ETS) as well as exposure to diesel exhaust particles (DEP) could promote allergic sensitization or aggravate symptoms of asthma, suggesting a role for these inhaled pollutants in the pathogenesis of asthma. Mouse models are a valuable tool to study the potential effects of these pollutants in the pathogenesis of asthma, with the opportun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
95
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 82 publications
(98 citation statements)
references
References 186 publications
3
95
0
Order By: Relevance
“…The sequence of cellular events may exacerbate asthma symptoms, as reflected in the allergic reactions. Furthermore, the recruitment of eosinophils in the lungs is primarily controlled by Th lymphocytes and is enhanced by cytokines (eg, IL-13); 38 infiltration is characteristic of airway inflammation during bronchial asthma. Lymphocytes, including T and B cells, are considered cells of the adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…The sequence of cellular events may exacerbate asthma symptoms, as reflected in the allergic reactions. Furthermore, the recruitment of eosinophils in the lungs is primarily controlled by Th lymphocytes and is enhanced by cytokines (eg, IL-13); 38 infiltration is characteristic of airway inflammation during bronchial asthma. Lymphocytes, including T and B cells, are considered cells of the adaptive immune system.…”
Section: Discussionmentioning
confidence: 99%
“…26 Other effects include allergic reaction, nasal cavity inflammation and damage, pharyngeal problems, larynx damage, and influenza-like illness. 27,28 After passing the lung, the particles merge into the blood and cause erythrocyte damage. Most damages were characterized by changes of the geometrical dimension of the erythrocytes.…”
Section: -7mentioning
confidence: 99%
“…Exposure to DEP promotes sensitization toward coinhaled allergens and aggravates asthma (2). To investigate the molecular mechanisms, we set up a model wherein we exposed mice to saline, DEP or HDM alone, or combined DEP and HDM (experimental protocol in Fig.…”
Section: Role Of Chemr23 Signaling In a Model Of Dep-induced Lung Infmentioning
confidence: 99%
“…Experimental studies in mice showed that exposure to DEP can enhance allergic airway responses, including eosinophilia, goblet cell metaplasia, and T H 2 production (2). In addition, in controlled human exposure studies, combined exposure to DEP plus allergens increased allergen-specific Ig levels and induced a T H 2 cytokine pattern (2,3). The mechanistic basis of the inflammatory response in the lung to DEP inhalation and the adjuvant response to DEP on allergen-induced airway inflammation remain incompletely known.…”
mentioning
confidence: 99%